SEG Technical Program Expanded Abstracts 2003 2003
DOI: 10.1190/1.1817547
|View full text |Cite
|
Sign up to set email alerts
|

Dual simulations of fluid flow and seismic wave propagation in a fractured network: Effects of changes in pore pressure on signature of seismic waves

Abstract: Fluid flow in the Earth's crust plays an important role in a number of geological processes, and such flow is usually believed to be controlled by open macro-fractures in at least carbonate reservoirs. The movement of fluids in the fractured media will result in changes on the pore pressure and consequently will cause changes to the effective stress, traction and elastic properties. The main purpose of this study is to examine the effect of pore pressure changes on seismic wave propagation (i.e. amplitude, fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…After set up, fractures are generated, constrained to the seismic data in a leastsquares sense. These seismic fracture attributes can then be used as the primary input for advanced fracture modelling tools and for fluid flow simulation Vlastos et al 2003;Liu et al 2004). Whilst the determination of meaningful fracture attributes from seismic data is not a trivial process and the route is still, as yet, uncertain, the seismic-fracture model methodology has provided a way of addressing the interwell uncertainty present in most fractured reservoir models.…”
Section: From Seismic Data To Reservoir Simulation: Discrete Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…After set up, fractures are generated, constrained to the seismic data in a leastsquares sense. These seismic fracture attributes can then be used as the primary input for advanced fracture modelling tools and for fluid flow simulation Vlastos et al 2003;Liu et al 2004). Whilst the determination of meaningful fracture attributes from seismic data is not a trivial process and the route is still, as yet, uncertain, the seismic-fracture model methodology has provided a way of addressing the interwell uncertainty present in most fractured reservoir models.…”
Section: From Seismic Data To Reservoir Simulation: Discrete Fracturementioning
confidence: 99%
“…Finally, it is suggested that seismic fracture attribute maps can be used to constrain reservoir fracture models using the concept of a discrete fracture network (DFN) model (Rogers et aI. 2003;Vlastos et al 2003).…”
mentioning
confidence: 99%